(3NeQI CdMGf hQfI GdCdMGf aj TQM QSGdI GdTjN CQSdGfs - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s; (3GdTjN CQSdGfs ((3YHO GdcQje Hf Ydi GdTHGfHi GdLjRGhi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi WgQ bhdH ChdjGFI HejGg Gdjbjf CeG HYO ajbhd CSjQ GdPfhH YHO GdZfi Hf ESeGYjd Hf GdfGHdSi gPG TQM CeWQJg SeGhGJ EdgGei ddQSGdI Yf GdRgO gd gh Qcf fYJeO Ydjg s
(3BNQgG (B:s
(3hMci Yf CHj YHO Gddg Hf Naja Cfg bGd QCjJ GdfHi Udi Gddg Ydjg hSde ai GdefGe abGd di ef YQa WQjbkG Edi Gddg jSdcg Ke QLY Yfg YPHg Gddg YPGHkG de jYPH Hg CMOkG ef GdYGdejf gPG BNQ eGCQGO EjQGOg SjOfG Rjf GdYGHOjf GdYeQi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdJUha hGdBOGH GdTQYjIs